A feminist voyage through international relations - Tickner, J. Ann (New York Oxford University Press, 2014)
J. Ann Tickner is ranked among the most influential scholars of international relations. As one of the founders of the field of feminist international relations, she is also among the most pioneering. 'A Feminist Voyage through International Relations' provides a compendium of Tickner's work as a feminist IR scholar, from the late 1980s through to present day.
Includes bibliographical references and index.
Keywords: International relations; Security, International; Feminist theory -- Political aspects; Feminism -- International cooperation